Psycho-Educational Training on Existential Issues and Effects on Marital Satisfaction and Communication Among Iranian Women - Kalantarkousheh, Seyed Mohammad (2011)
Increasing the quality of marital satisfaction and communication is a paramount concern among family counselors and psychologists. Issues that are important in the quality of marital satisfaction and communication are discussed in the four existential counseling theories as well. However, there is a lack of effort made to extract and apply the important existential issues from the four existential counseling theories to improve the quality of married life. In fact, there has been no research done to examine the effects of existential issues on marital satisfaction and communication. To fill this gap, this study examines the effects of existential issues through psycho-educational training on marital satisfaction and communication among married Iranian women. This study was performed as an experimental design with pre-, post-, and follow-up tests, random assignment, and control group. The population of this study consisted of all married women referred to the researcher from two health centres in the municipality of Tehran in Iran. The experimental group received training based on the existential issues extracted from the four existential counseling theories. Instruments for data collection included marital satisfaction and communication subscales of ENRICH besides the demographic questionnaire, which were completed by the participants in the experimental and control groups three times. The main hypotheses were whether there would be significant differences in marital satisfaction and communication of the experimental group and the control group in pre-test, post-test and follow-up test. The collected data were coded and then analyzed using SPSS version 18. The results of repeated measure ANOVA for the marital satisfaction indicated that there was a statistically significant difference in the mean score of marital satisfaction over time for the experimental group, i.e. F (1, 29) = 110.51, p<.05, ηp2 =.79, F=1.28. Additionally, running repeated measure ANOVA for marital communication revealed that there was a significant difference in the mean score of marital communication over time for the experimental group, i.e. F (1, 29) = 80.38, p<.05, ηp2 =.73, F=1.06. Furthermore, running an independent sample t-test to compare mean score of follow-up test of marital satisfaction and communication in the experimental and control groups showed a significant difference in the mean score between the experimental group and the control group in both marital satisfaction and communication. Therefore, the findings provided evidence that the training based on existential issues revealed positive effects on marital satisfaction and communication and improved marital satisfaction and communication of married Iranian women. Moreover, the findings of this study have implications for family counselors, couple counselors and for marriage trainers. Specifically, there is indication that psycho-educational training of existential issues can be efficiently conducted among married Iranian women to improve quality of marital life. However, further study to replicate the findings in different areas and cultures for generalization is needed.